Traditional corporate reporting in the era of integrated reporting: views of accounting practitioners in Bangladesh / Abdul Alim Baser and Mazni Abdullah - Baser, Abdul Alim; Abdullah, Mazni (UiTM Press, 2024)
This paper explores the accounting practitioners’ views on traditional corporate reporting during the integrated reporting (IR) era in Bangladesh. Semi-structured interviews with professional accountants in Bangladesh were conducted to gauge their insights on traditional corporate reporting practices. Using stakeholder theory, the findings of the interviews indicate that traditional corporate reporting in Bangladesh is insufficient and less reliable for stakeholders’ decision-making. The reliability of traditional corporate reporting is largely compromised due to the absence of due diligence by the preparers. Yet, this is still practiced due to regulatory compulsions in Bangladesh. Moreover, the preference for financial information by investors also mildly catalyses the current practice. The findings of this study imply the need for better reporting in place of traditional corporate reporting. It thus signifies the worth of IR as a better corporate reporting model.